DEVELOPMENT AND VALIDATION OF A UV-SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF CEPHALEXIN MONOHYDRATE IN HUMAN PLASMA - Auwal, M.A; Musa, A; Yakasai, I.A; Adamu, S.A; M. A. Usman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
A simple, rapid and precise spectrophotometric method has been developed for the determination of cephalexin monohydrate in plasma. The method was developed via scan of a standard cephalexin solution at a concentration of 15 μg/ml and obtained a λmax of 261 nm and validated in terms of linearity, accuracy and can be applied for routine estimation of cephalexin monohydrate powder. This method utilized 40 % perchloric acid to precipitate plasma proteins after spiking the plasma with different aliquots of cephalexin standard solution. The supernatant of this solution was measured at 261 nm (λmax) after buffering with phosphate buffer (pH 4) and volume adjustment with distilled water post-centrifugation to construct a 10 point calibration curve. It was linear in the range of 5-150 μg/ml with a correlation coefficient of 0.9994 and the percentage recovery was found to be 84-85.5 %.